Typification of the name Hypochaeris facchiniana Ambrosi (Asteraceae) - Orsenigo, Simone; Galasso, Gabriele; Bonomi, Costantino (Phytotaxa, 2019)
The present contribution is related to the project “Italian loci classici census”, promoted by the Italian Botanical Society and aimed at typifying all the names of the taxa described from Italy and at increasing their systematic knowledge (Domina et al. 2012, Passalacqua et al. 2014, Peruzzi et al. 2015, Brundu et al. 2017).